2021
DOI: 10.1161/jaha.121.021090
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acute Exposure to Altitude on the Quality of Chest Compression‐Only Cardiopulmonary Resuscitation in Helicopter Emergency Medical Services Personnel: A Randomized, Controlled, Single‐Blind Crossover Trial

Abstract: Background Helicopter emergency medical services personnel operating in mountainous terrain are frequently exposed to rapid ascents and provide cardiopulmonary resuscitation (CPR) in the field. The aim of the present trial was to investigate the quality of chest compression only (CCO)‐CPR after acute exposure to altitude under repeatable and standardized conditions. Methods and Results Forty‐eight helicopter emergency medical services per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
3
2
0
Order By: Relevance
“…The authors analyze a secondary objective of a previous study that showed a reduction of chest compression (CC) depth at altitude [ 2 ] and show that heart rates are significantly higher at altitude before and after CPR. Such results support the results of a study that we recently published [ 3 ] as well one of Sato et al [ 4 ], where we both observed a significant decrease in peripheral oxygen saturation, an increase in heart rate, as well as an increase in fatigue during CPR at 3000 and 5000 m, and 3700 m, respectively. Conversely to Niederer et al, the forty-eight participants in our study, all helicopter emergency medical services (HEMS) providers, reached altitudes without physical effort simulating a rapid helicopter ascent in a hypobaric chamber [ 3 ].…”
supporting
confidence: 93%
See 3 more Smart Citations
“…The authors analyze a secondary objective of a previous study that showed a reduction of chest compression (CC) depth at altitude [ 2 ] and show that heart rates are significantly higher at altitude before and after CPR. Such results support the results of a study that we recently published [ 3 ] as well one of Sato et al [ 4 ], where we both observed a significant decrease in peripheral oxygen saturation, an increase in heart rate, as well as an increase in fatigue during CPR at 3000 and 5000 m, and 3700 m, respectively. Conversely to Niederer et al, the forty-eight participants in our study, all helicopter emergency medical services (HEMS) providers, reached altitudes without physical effort simulating a rapid helicopter ascent in a hypobaric chamber [ 3 ].…”
supporting
confidence: 93%
“…Such results support the results of a study that we recently published [ 3 ] as well one of Sato et al [ 4 ], where we both observed a significant decrease in peripheral oxygen saturation, an increase in heart rate, as well as an increase in fatigue during CPR at 3000 and 5000 m, and 3700 m, respectively. Conversely to Niederer et al, the forty-eight participants in our study, all helicopter emergency medical services (HEMS) providers, reached altitudes without physical effort simulating a rapid helicopter ascent in a hypobaric chamber [ 3 ]. Nevertheless, we also observed an increase in heart rate during CPR that was even bigger compared to the one observed by Niederer et al and was dependent on the altitude reached.…”
supporting
confidence: 93%
See 2 more Smart Citations
“… 10 However, it is not known whether mask wearing at higher altitudes, either at rest or during physical activity, may influence blood gases to a greater extent. In such circumstances, hypoxaemia may impair physical 11 and cognitive performance, 12–14 negatively affecting work performance and occupational health, as well as increasing the risk of accidents. Besides hypoxaemia, wearing a mask may cause discomfort, affect wellbeing and challenge heat dissipation during exercise or hot weather conditions (while hypoxia further increases perceived exertion), which in turn may interfere with work performance or wearing adherence.…”
Section: Introductionmentioning
confidence: 99%